Discovery and SAR of aryl hydroxy pyrimidinones as potent small molecule agonists of the GPCR APJ. Issue 7 (1st April 2020) - Myers, Michael C.; Bilder, Donna M.; Cavallaro, Cullen L.; Chao, Hannguang J.; Su, Shun; Burford, Neil T.; Nayeem, Akbar; Wang, Tao; Yan, Mujing; Langish, Robert A.; Dabros, Marta; Li, Yi-Xin; et al.
Graphical abstract: Abstract: This article describes the discovery of aryl hydroxy pyrimidinones and the medicinal chemistry efforts to optimize this chemotype for potent APJ agonism. APJ is a G-protein coupled receptor whose natural agonist peptide, apelin, displays hemodynamic improvement in the cardiac function of heart failure patients. A high throughput screen was undertaken to identify small molecule hits that could be optimized to mimic the apelin in vitro response. A potent and low molecular weight aryl hydroxy pyrimidinone analog 30 was identified through optimization of an HTS hit and medicinal chemistry efforts to improve its properties.